2007
DOI: 10.1093/ecam/nem005
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Medicine: A Cognitive and Epistemological Review

Abstract: In spite of the common belief that Chinese natural philosophy and medicine have a unique frame of reference completely foreign to the West, this article argues that they in fact have significant cognitive and epistemic similarities with certain esoteric health beliefs of pre-Christian Europe. From the standpoint of Cognitive Science, Chinese Medicine appears as a proto-scientific system of health observances and practices based on a symptomological classification of disease using two elementary dynamical-proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 25 publications
2
24
0
Order By: Relevance
“…Our results indicated that GBF suppresses cancer cell attachment to ECM components in a non-toxic concentration. The suppression of tumor cell migration in human lung cancer H1299 cells by guava leaves reported previously (21) is in agreement with some of our results. Several studies indicated that MAPKs including ERK1/2, p38 MAPK, and SAPK/JNK play a critical role in regulating the expression of MMPs (4).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our results indicated that GBF suppresses cancer cell attachment to ECM components in a non-toxic concentration. The suppression of tumor cell migration in human lung cancer H1299 cells by guava leaves reported previously (21) is in agreement with some of our results. Several studies indicated that MAPKs including ERK1/2, p38 MAPK, and SAPK/JNK play a critical role in regulating the expression of MMPs (4).…”
Section: Discussionsupporting
confidence: 94%
“…We further found that GBF reduced the constitutive expression of both MMP-9 and MMP-2 mRNAs and proteins. Our results are in agreement with a previous report that the aqueous extract of Psidium guajava budding leaves can downregulate MMP-2 and MMP-9 expressions (21). In addition, we found that GBF failed to suppress the expression of the CXCR4, which has been implicated in the metastasis of non-small cell lung carcinoma (22), suggesting GBF exerts antimetastatic potential by blocking MMP-2 and MMP-9 expressions and activities.…”
Section: Discussionsupporting
confidence: 93%
“…The combination is termed 'herb pairs' just like parents for the effective action. 4) When a crude drug effective for a certain condition is discovered, it is scientifically analyzed to identify the active ingredient from which the effect is derived in pharmacognosy. The isolated ingredient may be used as a new drug or serve…”
Section: Difference Between Pharmacognosy and Wakan-yaku Sciencementioning
confidence: 99%
“…In addition, the combination of 2 crude drugs ( , herb pairs) can also form the basic structure of prescriptions as described above, referred to as family. 4) Furthermore, the effective direction of the original fundamental prescriptions, which has the basal effect of the family, is emphasized or changed by adding a new crude drug ( ). For example, 'Keishito' combined with pueraria root (kakkon) and ephedra herb becomes Kakkonto, and its body-warming activity is strengthened.…”
Section: Historical and Traditional Theories Supporting Wakan-yaku: Wmentioning
confidence: 99%
“…Acupuncture is part of Traditional Chinese Medicine (TCM), which in itself is a form of CAM that is based on thousands of years of practice [21]. One of the features of the TCM approach is the individualization of treatment, which relies on a symptom-based diagnostic process [22].…”
Section: Introductionmentioning
confidence: 99%